Study of Catalytic Sites on Ruthenium For Hydrogenation of N-ethylcarbazole: Implications of Hydrogen Storage via Reversible Catalytic Hydrogenation - Eblagon, K; Tam, K; Yu, K; Zhao, S; Gong, X; He, H; Ye, L; Wang, L; Ramirez-Cuesta, A; Tsang, S (2010)
Hydrogen storage is a significant challenge for the development and viability of hydrogen-powered vehicles. Storage of molecular hydrogen in nitrogen-substituted polyunsaturated aromatic organic molecules through reversible catalytic hydrogenation and dehydrogenation is a promising approach. The success of developing a catalytic hydrogen storage concept is highly dependent on finding an efficient catalyst; however, understanding how molecules interact with metal catalytic sites is, at present, rather limited. In this work, a combined experimental and theoretical study is conducted to identify efficient catalytic sites on metallic surfaces and to understand the reaction mechanism for the forward hydrogenation reaction. It is clearly revealed from experimentation that hydrogenation of N-ethylcarbazole, a typical nitrogen-substituted polyunsaturated aromatic organic molecule, is taking place in a stepwise manner over metal catalysts. Because of steric constraints at terrace sites, the kinetically stable pyrrole intermediate, formed by partial hydrogenation of N-ethylcarbazole, cannot be readsorbed once desorbed into solution. Therefore further hydrogenation occurs at the low coordinated sites where no similar steric hindrance is encountered. Thus, the mechanism for hydrogenation involves an unusual shuttling of partially hydrogenated intermediates from terrace sites to higher indexed sites via solution. First-principles calculations confirm that the pyrrole intermediate can strongly adsorb to various low coordination sites, typically steps on the vicinal (109) surface, while the adsorption is extremely weak on flat (001) terraces. This work is the first example of catalytic site analysis to account for observed activity, selectivity and recyclability of a typical metal catalyst for catalytic hydrogen storage, which could lead to rational design of superior materials. © 2010 American Chemical Society.